Lesne polioze listavcev - Tišler, Vesna (Zbornik gozdarstva in lesarstva, 2000)
The article studies hardwood polyoses (hemicelluloses), being one of renewablenatural organic materials, next to cellulose. Hardwood polyoses differ from softwood ones with regard to their content and composition; their portion in hardwoods being up to 40%. Polyoses could be converted to primary chemicals: xylose, xylitol, furfural, hydroxymethylfurfural, levulinic acid, etc. To use wood polyoses successfully we have to understand their chemical structure well.
Keywords: hemiceluloza; les; listavci; polisaharidi; sestava